Evaluating the impact of climate change based on herders' observations and comparing it with hydro-climatic and remote sensing data - Jigjsuren, Odgarav, author; Baival, Batkhishig, author; Nayanaa, Kherlentuul, author; Jargalsaikhan, Azjargal, author; Dash, Khurelbaatar, author; Badamkhand, Bayarmaa, author; Bud, Amarzaya, author; Nutag Action and Research Institute, publisher (Colorado State University. Libraries, 2015)
Studying the impact of recent years' climate change on Mongolian rangeland livestock husbandry and on pastoral herders' livelihoods, based on herders' observations and their experience, is an approach that is of considerable interest to many scientists. Our research identifies changes in natural conditions and climate, as well as the changes in rangeland conditions, as observed by herders, and compares them against weather stations' multi-year observations and remote sensing data. Our research region of Khanbogd, Manlai and Bayan-Ovoo soums of Umnugobi aimag has been, in the recent years, experiencing a rapid development of the mining industry and human population growth. According to local herders, current rangeland quality greatly decreased compared to the period before the year 2000, while the area of barren land, sand movement and soil erosion increased. Herders also said that the amount of rainfall diminished and the rainy season's duration shortened, short high intensity rains grew in number, and it became extremely hot in summer. Soum weather station records of air temperature, precipitation and evaporation confirmed herders' observations, and were consistent with Normalized Difference Vegetation Index (NDVI) or the results of observations of rangeland vegetation phenology. To develop local adaptive capacity in the face of changing social-ecological systems it is important to use and integrate multiple sources of information that are essential for making policy implementation mechanisms and measures more locally appropriate and relevant.
Comparing herders' observations of climate change impacts with weather and remote sensing data
Presented at the Building resilience of Mongolian rangelands: a trans-disciplinary research conference held on June 9-10, 2015 in Ulaanbaatar, Mongolia.
Keywords: herders' observations; climate change; rangeland degradation